A universal strategy for multicolor organic circularly polarized afterglow materials with high dissymmetry factors - Chenjia Yin; Siyu Sun; Zi-Ang Yan; Honglong Hu; Ping Jiang; Zhuoran Xu; He Tian; Xiang Ma (Proceedings of the National Academy of Sciences, 2025)
Materials with pure organic circularly polarized afterglow (CPA) have attracted significant attention due to their spatiotemporal-resolved optical properties, yet achieving simultaneous high dissymmetry factor (glum) and multicolor ultralong emission remains a challenge. Here, we establish a universal energy transfer-photon coupling strategy to realize CPA spanning from blue to red with record-high glum (up to 1.90) and ultralong lifetimes (>6 s). Systematic characterization of nonchiral donor–acceptor systems (TP-BPEA, TP-Fluo, etc.) reveals the absence of ground-state chiral centers ( g CD ≈ 0) and orientation artifacts ( LD < 10 −7 ), confirming the key role of cholesteric liquid crystal polymer in chirality induction. This spatiotemporal synergy between energy transfer (wavelength modulation) and photonic engineering (polarization control) provides a framework for chiral photonic materials, with potential implications for multidimensional information encryption.